Becoming a homeowner in Britain in the 1990s - John Ermisch; Brendan Halpin (University of Essex, Institute for Social and Economic Research (ISER), 2000)
We model the hazard of first entry to owner occupation, using a sub-sample of the British Household Panel Study consisting of young adults not yet in owner occupation. Our interest is to assess the importance of social inequality, measured as socio-economic class using the new ONS-SEC, while taking account of the direct effects of age, household formation, education and labour market situation of the individual (and his/her spouse, where appropriate). Socio-economic class has a very strong bivariate effect but this persists, with some modification, into the multivariate analysis. Higher professionals and managers have by far the highest rate of entry, with the unemployed and students having the lowest, even when controlling for income, education, employment status, age, gender and household formation, all of which have strong effects of their own. On a smaller sample we investigate some effects of class of origin, and of spouses class but with few significant effects. Some features of this modelling lead us to speculate that access to social housing, as a competing destination, may be patterning entry to owner occupation. The class gradient may reflect as much the compensatory effects of state provision as market-related advantages. Also, the effect of childen on entry to owner occupation is strongly negative. We investigate this by fitting parallel models on the rate of entry to social housing, and find that this seems to be the case: while the age and partnership effects are very similar, the class effect is reversed (except for students, whose low rate of entry to ownership is not associated with disadvantage) and the effect of children is strong and positive.
Keywords: 330